1991
DOI: 10.1080/00071669108417328
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic observations on the intestinal villi in growing white leghorn and broiler chickens from 1 to 30 days of age

Abstract: 1. To obtain intestinal morphological data demonstrating the faster growth rate in broiler (BR) than in White Leghorn (WL) chickens, villi of the duodenum, jejunum and ileum were examined from 1 to 30 d of age by scanning electron microscopy. 2. At the first day after hatching, villi of each intestinal segment showed a finger-like shape in both breeds. Villi developed to a plate-like shape in the duodenum, a wave-like shape in the jejunum and a tongue-like shape in the ileum at 30 d of age via the common plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 20 publications
11
41
1
3
Order By: Relevance
“…On the contrary, it is likely that epithelial replacement occurs faster in broilers than in white leghorn chickens. Differences in the villus morphology and activities have been shown in that the villus epithelia develop more over the whole apical surface, have larger villi and wider microvilli [29] and show an earlier maturation in activities [30] in the broiler than in white leghorn chickens. Therefore, although the infected broilers had more severe intestinal lesions (at day 2 PI) because of the presence of more differentiated epithelia, the recovery might be faster due to a faster replacement of the epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it is likely that epithelial replacement occurs faster in broilers than in white leghorn chickens. Differences in the villus morphology and activities have been shown in that the villus epithelia develop more over the whole apical surface, have larger villi and wider microvilli [29] and show an earlier maturation in activities [30] in the broiler than in white leghorn chickens. Therefore, although the infected broilers had more severe intestinal lesions (at day 2 PI) because of the presence of more differentiated epithelia, the recovery might be faster due to a faster replacement of the epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…PATHOBIOLOGY Shapiro et al (1998) have shown that broilers are more susceptible to MAS than are Leghorn chickens and turkey poults. Contrary to layer chickens, broilers have a faster development of intestinal morphology and activities (Yamauchi and Isshiki, 1991;Yamauchi et al, 1992). The difference in severity of the intestinal lesions and the reduction in body weight gain among genetic lines of commercial broiler chicks reflected the difference in susceptibility to MAS between broiler lines (Songserm et al, 2002a).…”
Section: Pathogenesismentioning
confidence: 99%
“…Although there is a lack of agreement on the pattern of development of these parameters in mammals (20), in chickens all reports (16,30) find these parameters to be increased during development.…”
Section: Discussionmentioning
confidence: 99%
“…At hatch, intestinal morphology (16,30), digestive function (27), and nutrient transport capacity (2) have attained a state of complete development. The maximal capacity per tissue weight to transport monosaccharides is reached the day after hatch and declines afterward until attainment of adult levels at the age of 5 wk (18,25).…”
Section: Discussionmentioning
confidence: 99%